Ortopedik Aciller Tanı ve Tedavi Kılavuzu - Gencer, Elif Nur; Çulcu, Ahmet; Süer Doğan, İhsaniye; Yiğit, Alperen; Yeni, Teoman Bekir; Çamoğlu, Can; Ülgen, Nuri Koray; Fakıoğlu, Remzi Can; Kıran, Veli Can; Arslan, Mehmet Murat; Mert, Orhan; Sarı, Soner; et al. (2023)
-